Feline herpesvirus 1 viral load related to environmental factors in sheltered cats - Natasha Baumworcel; Joylson de Jesus Pereira; Ana Maria Barros Soares; Guilherme Nunes Souza; Nadia Regina Pereira Almosny; Tatiana Xavier de Castro (Ciência Rural)
ABSTRACT: Shelter environment stress factors are related to FHV-1 viral reactivation. However, comparisons between conjunctival viral load and environmental factors have not been commonly evaluated. The aim of this study was to correlate FHV-1 viral load in domestic cats with and without clinical signs of conjunctivitis to shelter design in order to use FHV-1 viral load as a parameter of “health management”. Cats from four different shelters underwent an ophthalmological examination. Samples were collected by rolling a DNA/RNAse-free cytobrush over the ventral conjunctival fornix and were stored in 1.5 mL sterile microtubes in 500 μL of Eagle’s minimum essential medium and kept at 4 ºC. Molecular procedures were performed up to 48 hours after collection. Different routines regarding new arrivals were directly related to FHV-1 viral load. Shelters where new arrivals occurred on daily basis had the highest viral load (2.69x108 copies/µL), while those shelters where new arrivals had not occurred in the few months prior to the beginning of the study had the lowest rate (1.63x103 copies/µL). Environmental factors directly influenced FHV-1 DNA viral load. This study highlighted the need to improve the management approach in the animal shelter environment to reduce stressful situations responsible for FHV-1 reactivation and higher viral load quantification.